2020
DOI: 10.1096/fasebj.2020.34.s1.09926
|View full text |Cite
|
Sign up to set email alerts
|

Selective Breeding in Domestic Dogs: How Selecting for a Short Face Impacted Canine Neuroanatomy

Abstract: Domestic dogs (Canis lupus familiaris) exhibit a wide range of cranial morphologies. This diversity in skull shape is largely the result of modern selective breeding practices. This project investigates the impact of selection for facial reduction on canine neuroanatomy. Previous research has indicated that the breeding for reduced faces in dogs has led to global impacts in the shape of their skull and mandible. This previous research has largely failed to consider, however, the impact of these breeding practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Located on the epithelium of the olfactory turbinals are sensory neurons populated with olfactory receptors, which receive airborne odorants and transmit odor signals via nerve bundles through the cribriform plate to the olfactory bulb of the brain (Evans, 1993). One recent study has shown that artificial selection for short snouts has noticeably impacted the neuroanatomy of these short-faced breeds, and especially the shape of the olfactory bulb (Selba et al, 2021), which is nested in and tightly associated with the cribriform plate (Evans, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Located on the epithelium of the olfactory turbinals are sensory neurons populated with olfactory receptors, which receive airborne odorants and transmit odor signals via nerve bundles through the cribriform plate to the olfactory bulb of the brain (Evans, 1993). One recent study has shown that artificial selection for short snouts has noticeably impacted the neuroanatomy of these short-faced breeds, and especially the shape of the olfactory bulb (Selba et al, 2021), which is nested in and tightly associated with the cribriform plate (Evans, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…One consistent feature of brachycephalic dogs and cats is the shortening of the cranial base and a reduced cranial capacity that can cause overcrowding (i.e., a larger total brain volume relative to body weight) and brain herniation ( Carrera et al 2009 ; Schmidt et al 2013 , 2014 ; Selba et al 2020 ; Sokołowski et al 2020 ). It has been suggested that this volumetric restriction in brachycephalic dogs also leads to a more ventrally rotated longitudinal brain axis, i.e., progressive ventral pitching of the brain, as well as a more ventrally shifted olfactory bulb position ( Roberts, McGreevy and Valenzuela 2010 ; Hussein, Sullivan and Penderis 2012 ).…”
Section: Pathological and Morphological Correlates Of Brachycephalymentioning
confidence: 99%
“…the length of the cranium is shorter than the width) are worse in olfactory detection than breeds with mesocephalic or dolichocephalic skulls (Polgár et al, 2016), but see (Hall et al, 2015). It has been argued that selective breeding for reduced faces not only resulted in functional anatomical changes in the nose, but in a reduction in brain matter devoted to olfaction and spatial reorganisation of the brain (Selba et al, 2021). While a reduction of olfactory cortical areas clearly impacts the associated functions, such as olfactory detection and discrimination, the impact of spatial reorganisation of the brain areas and associated functions are currently investigated: Anatomical differences between breeds as a result of selective breeding and reflected in the cepahlic index have been reported (Hecht et al, 2019; Selba et al, 2021).…”
Section: Discussionmentioning
confidence: 99%